SIFAT DHATIYAH ALLAH PERSPEKTIF IBN JARIR AL-TABARI DALAM TAFSIR JAMI AL-BAYAN - Solahudin, Solahudin; Yasyakur, Moch; Sarifudin, Agus; Thalib, Muhammad (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to examine the Quranic verses related to the attributes of Allah using a thematic exegesis approach. The main focus of the research is to understand the names and attributes of Allah mentioned in the Quran, which form the foundation of Islamic faith. The research uses a qualitative method with textual and semantic approaches to explore the meanings embedded in the Quranic texts and Hadiths. The primary data sources are the exegesis Jāmi’ al-Bayān fī Ta’wīl al-Qur`ān by Ibn Jarīr al-Ṭabarī and other relevant literature. The findings show that recognizing the names and attributes of Allah in the Quran enhances understanding of tawhid (monotheism) and devotion to Him. Quranic verses containing the names and attributes of Allah emphasize His rubūbiyah (lordship), al-karām (generosity), and al-‘ilm (knowledge) that must be believed and practiced. According to al-Ṭabarī, Allah’s attributes reflect His perfection, including mercy, knowledge, power, wisdom, and majesty, all of which demonstrate His greatness and supremacy. This study underscores the importance of understanding the attributes of Allah to strengthen faith and enhance devotion in worship.